Aplikasi Maṣlaḥah Mursālah Dalam Perluasan Takrifan Asnaf Zakat Dan Kesannya Dalam Mendepani Krisis Kemiskinan Di Malaysia : (The Application of Maṣlaḥah Mursālah in Expanding the Definition of Zakat Recipients And Its Impact on Addressing Poverty Crisis in Malaysia) - Harun, Muhammad Safwan; Hasim, Hafizi Zikry; Rosele, Muhammad Ikhlas; Ali, Abdul Karim (Online Journal of Research in Islamic Studies, 2023)
Changing times have led to the emergence of contemporary issues on Islamic jurisprudence (fiqh) without specific legal evidence (nas hukum). Consequently, they use of alternative legal sources, which is maṣlaḥah mursālah to solve the issues. Maṣlaḥah mursālah is an instrument employed by scholars (fuqaha) to address Islamic legal issues lacking specific evidence. In the context of zakat distribution management, certain categories of recipients (asnaf), especially those related to fi sabilillah, are observed to no longer exist due to the absence of ’illah (legal cause) for these recipients. To enhance productivity in zakat distribution, scholars engage in ijtihad, considering maṣlaḥah mursālah as one of the arguments for expanding the definition of these recipients. Therefore, this article evaluates the application of maṣlaḥah mursālah as a rationale for broadening the definition of fi sabilillah recipients based on criteria established by fuqaha. It also assesses the effects of expanding the definition of fi sabilillah recipients in addressing contemporary poverty crises. The qualitative research conducted focuses solely on fi sabilillah recipients. The findings indicate that the use of maṣlaḥah mursālah in expanding the definition of recipients has a significant impact on the quantity of zakat distribution. In a nut shell, authorities should reconsider the consequences of broadening the definition of zakat recipients in the present context, prioritizing more deserving recipients to alleviate poverty.